2018
DOI: 10.3390/ijgi7020057
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gross Primary Production (GPP) over the Past Two Decades Due to Land Use Conversion in a Tourism City

Abstract: Understanding the changes in gross primary production (GPP), which is the total carbon fixation by terrestrial ecosystems through vegetation photosynthesis, due to land use conversion in a tourism city is important for carbon cycle studies. Satellite data from Landsat 5, Landsat 7 and Landsat 8 and meteorological data are used to calculate annual GPP for 1995, 2003 and 2014, respectively, using the vegetation production model (VPM) in the tourism city Denpasar, Bali, Indonesia. Five land use types generated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 96 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…In Brazil, one of the leading meat producers globally, cattle-associated deforestation is responsible for 90% of land changes (Margulis 2004) and up to 41% of all deforestation in the Brazilian Amazon (Erasmus et al 2020). The conversion of forests into hotels, restaurants and other forms of entertainment as well as to residential areas to accommodate the increasing number of people who migrate to work in the tourism sector represent also tourism-induced land changes (Lhota, Scott, and Sha 2019; Nuarsa et al 2018).…”
Section: The Potential Role Of Tourism In the Development Of Emerging...mentioning
confidence: 99%
“…In Brazil, one of the leading meat producers globally, cattle-associated deforestation is responsible for 90% of land changes (Margulis 2004) and up to 41% of all deforestation in the Brazilian Amazon (Erasmus et al 2020). The conversion of forests into hotels, restaurants and other forms of entertainment as well as to residential areas to accommodate the increasing number of people who migrate to work in the tourism sector represent also tourism-induced land changes (Lhota, Scott, and Sha 2019; Nuarsa et al 2018).…”
Section: The Potential Role Of Tourism In the Development Of Emerging...mentioning
confidence: 99%
“…Recently, creating perfect urban facilities and services that guarantee smooth tourism activities has gathered increased attention, and an excellent tourism environment can enhance tourists' satisfaction and loyalty to the destination ( 11 13 ). However, rapid urbanization has also caused noticeable negative impacts, such as reduction of marine biodiversity, increased urban heat island effect, destruction of the ecological environment, and a decline in air quality ( 14 18 ). Furthermore, some studies have shown that the efficacy of tourism urbanization is affected by spatial planning ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…GPP is the total value of carbon fixation by terrestrial ecosystems through vegetation photosynthesis in a certain period [7]. GPP is considered to be very efficient to know and understand the variation of the coral productivity of vegetation in carbon sequestration in the atmosphere and its relationship to changes around mangrove forests, the increase in Co 2 in the atmosphere and climate change [8].…”
Section: Introductionmentioning
confidence: 99%